Effect of Temperature and Time on Thermal Disinfestation of Green Gram - Singh, K K; Kotwaliwale, N; Singh, Ranjeet (Journal of Agricultural Engineering, 2009)
Insect infestation accounts for majority of losses during storage of green gram. Chemical methods to prevent these losses, though effective and widely used, lead to undesirable consequences. The present study was initiated to explore possibility of using thermal disinfestation technique to control insect-pests. The exposure temperature and time to attain 100% mortality of insects (Callosobruchus Chinensis L.) and eggs in green gram were studied. The different optimum temperature and time combinations for mortality of insects were found as 50degree C–5 min, 55degree C–1 min, and 60degree C–45 s. However, 55degree C–300 s and 60degree C–120 s were suitable for 100% egg mortality.